Synthesis and Pharmacological Screening of Novel Ethyl(5-Substituted Acetamido)-3-methylthio-1-(4-chlorophenyl)-1H-pyrazole-4-carboxylate - Abubakkar, S.K.; Minhaj, S.D.; Baheti, K.G. (Asian Journal of Chemistry, 2012)
Several novel ethyl(5-substituted acetamido)-3-methylthio-1-(4-chlorophenyl)-1H-pyrazole-4- carboxylate were synthesized and screened for their analgesic activity at a dose of 50 mg/kg and 10 mg/kg by acetic acid induced writhing method and hot plate method respectively. The compound 5j and 5k are prominent candidates, which showed good analgesic activity among the series. The compound 5j and 5k showed 54.20 % and 52.22 % analgesic activity to that of standard aspirin by acetic acid induced writhing method whereas 72.88 % and 69.7 % analgesic activity to that of standard pentazocine HCl by hot plate method respectively.